Equilibrium Sorption Studies of Basic Blue-9 Dye from Aqueous Medium Using Activated Carbon Produced from Water Hyacinth (Eichornia Crassipes) - Tarawou, Timi; Wankasi, D.; Jnr, Michael Horsfall (Journal of Nepal Chemical Society, 2013)
The study shows that water hyacinth could be used as novel raw material for the production of effective activated carbon for the adsorption (removal) of Basic Blue- 9 dye from aqueous solution. Optimum removal of 86% dye was obtained which decreased to 62% with an increase in concentration from 50 to 300mg/l, though sorption capacity was found to increase with an increase in concentration. Both Langmuir and Freundlich isotherms were suitable for describing the experimental data in this study with high regression coefficients (R2) of 0.9852 and 0.9905 respectively. The Langmuir maximum sorption capacity (qm) was found to be 421mg/g. It was further observed that the intensity of adsorption, n, was found to be 1.84 which shows that the sorption process was favourable. The equilibrium parameter, RL, value of 0.138 also shows that the adsorption of Basic Blue-9 dyes onto the activated carbon was favourable. The macropore and micropore diffusion constants show that the rate limiting step is the micropore diffusion stage since the micropore diffusion constant (Kid2) value of 0 is lower than the macropore diffusion constant (Kid) value of 0.2543, thus the rate of micropore diffusion is the slower step and the rate determining step. The study also showed that the sorption process was predominantly controlled by intra-particle diffusion, though film diffusion also played a significant role. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9254 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 67-74 Uploaded date: 12/5/2013